Potassium-Competitive Acid Blocker sebagai Alternatif Penghambat Pompa Proton untuk Mengatasi Gejala Gastroesophageal Reflux Disease: Sebuah Laporan Kasus Berbasis Bukti - Prabata, Adam; Prahasary, Adelia Nova; Govinda, Arya (UI Scholars Hub, 2024)
Gastric acid suppression is one of the main pillars of gastroesophageal reflux disease (GERD) treatment. Proton pump inhibitor (PPI) is the most used drug for suppressing gastric acid in GERD patients currently. Potassium- acid competitive acid blocker (PCAB) is a new class of drug which can be used as an alternative drug for suppressing gastric acid, so hypothetically, this drug could be an alternative of PPI for relieving GERD symptoms. However, the ability of PCAB for relieving GERD symptoms was not established, so this study was aimed to elucidate the ability of PCAB as an alternative drug of PPI for relieving GERD symptoms. Comprehensive literature searching was conducted in several databases such as PubMed, Embase, Cochrane, EBSCO, and Proquest with keywords “GERD”, “PCAB”, “PPI” dan “symptoms” on September 16-20, 2023. Early literature searching comprised 229 articles then selected based on clinical question and eligibility criteria to get 3 articles to be appraised critically. Vonoprazan, one of PCAB, was using as the main therapy in all of selected studies. Two randomized control trial (RCT) studies showed the non-inferiority of vonoprazan compared to PPI for relieving GERD symptoms. On the other hand, one systematic review and meta-analysis study showed that vonoprazan was superior than PPI for relieving GERD symptoms. This evidence-based case report (EBCR) shows that vonoprazan is non-inferior, even superior, compared to PPI for relieving GERD symptoms. Further, extensive, and larger researches is still needed to support this evidence and the using of PCAB as main and routine treatment for GERD patients.